Registration of 'Ho 02‐113' Sugarcane. Issue 1 (2nd November 2012) - Hale, Anna L.; Dufrene, Edwis O.; Tew, Thomas L.; Pan, Yong-Bao; Viator, Ryan P.; White, Paul M.; Veremis, John C.; White, William H.; Cobill, Robert; Richard, Edward P.; Rukavina, Hrvoje; Grisham, Michael P.
Abstract : 'Ho 02‐113' (Reg. No. CV‐148, PI 665695) sugarcane (a complex hybrid of S. officinarum L., S. spontaneum L., S. barberi Jeswiet, and S. sinese Roxb. Amend. Jeswiet) was released by the USDA‐ARS Sugarcane Research Unit working cooperatively with the Louisiana State University Agricultural Center and the American Sugarcane League of the USA. This high‐fiber sugarcane cultivar was released for use as a biofuel feedstock to fill the rising industry demand. Ho 02‐113 is a progeny of the cross SES 234 × 'LCP 85‐384' made in Houma, LA in 2001. The cultivar was selected at the USDA‐ARS research farm in Schriever, LA, evaluated in multiple locations, and harvested from six southern Louisiana locations in six plant‐cane, two first‐ratoon, two second‐ratoon, and two third‐ratoon replicated tests. Ho 02‐113 averaged 125.3 Mg ha −1 total cane (TC) on a wet‐weight basis, 12.8 Mg ha −1 total soluble solids (TSS), 32.8 Mg ha −1 total fiber (TF), and 45.3 Mg ha −1 total fiber and soluble solids (TFSS). These values were significantly higher than those for the leading high‐fiber sugarcane cultivar L 79‐1002, which averaged 102.7 Mg ha −1 TC, 9.6 Mg ha −1 TSS, 27.8 Mg ha −1 TF, and 37.4 Mg ha −1 TFSS. The cultivar is resistant to leaf scald [caused by Xanthomonas albilinenas (Ashby) Dawson] and smut (caused by Ustilago scitaminea H. and P. Sydow) in inoculated tests and showed no symptoms either of brown rust (caused by Puccinia melanocephala H. and P. Sydow) or mosaic (caused by either Sugarcane mosaic virus or Sorghum mosaic virus ) when exposed to high levels of natural inoculums.